Kemandirian Belajar Mahasiswa Melalui Blended Learning pada Mata Kuliah Metode Numerik - Putri Fitriasari; Tanzimah Tanzimah; Novita Sari (Jurnal Elemen, 2018)
This study aims to know the improvement of student self-regulated learning (SRL) through blended learning. The method used is a quasi-experimental design with nonequivalent pre-test and post-test control-group. The subjects were students of mathematics education in the University of PGRI Palembang which consists of 54 students. They were divided into two groups of samples, namely the experimental class and control class. Experiment class got blended learning treatment, while control class got conventional learning. Research instrument consists of students' initial ability (SIA) test and KBM questionnaire. Data were analyzed quantitative descriptive. The results show that the improvement of SRL who get blended learning is not better than students who get conventional learning.